Pre-Service Teachers' Teaching-Learning Conceptions and Their Attitudes towards Teaching Profession - Hilal Bilgin; Necdet Aykac (ÜNİVERSİTEPARK Limited, 2016)
The aim of this study is to evaluate the teaching and learning conceptions of pre-service teachers and their attitudes towards teaching profession in terms of some variables. The study was designed as a relational survey model. The sample of the study consists of 406 first grade and senior university students, namely pre-service teachers, studying in Turkey. Criterion sampling method was applied in order to select the participants. Data of the study was collected through the "Teaching-Learning Conceptions Scale" and "Attitudes towards Teaching Profession Scale". Descriptive statistics, t-test, ANOVA and correlation analyses were used to analyze the data. In order to analyze the data, descriptive statistics, t-test, ANOVA and correlation analyses were used. According to the results obtained from this study, pre-service teachers' constructivist teaching and learning conception are higher than their scores of traditional conception. Moreover, pre-service teachers' teaching and learning conceptions do not differ significantly in terms of gender and grade variables, whereas they differ significantly according to their departments. In addition, pre-service teachers' levels of professional attitude can be regarded as positive and their attitudes towards teaching profession differ significantly in terms of gender, grade and department variables. Lastly, it was concluded that there was a positive correlation between pre-service teachers' constructivist teaching, learning conceptions, and their attitudes towards teaching profession while a negative relationship was observed between their traditional conceptions and professional attitudes.